Performance Analysis of Procurement Service Unit Employees Using the Balanced Scorecard Growth and Learning Perspective - Gunawan, Syahrul (Golden Ratio of Data in Summary, 2021)
This research was conducted using a Balanced Scorecard approach on a learning and growth perspective with the aim of (1) identifying and analyzing the effect of work motivation, employee development, and work environment on the performance of employees at the Procurement Service Unit Office of Maros Regency and analyze the factors that have a dominant influence on employee performance.The data analysis used is descriptive to explain the characteristics of the respondents and the description of the research variables. Furthermore, quantitative data were analyzed using multiple regression analysis through the Statistical Package For Social Science (SPSS) program to obtain information about the influence of work motivation factors, employee development, and work environment on employee performance both simultaneously and partially.The results of testing the hypothesis in this study indicate that all independent variables have a positive and significant effect on the dependent variable. The magnitude of the influence exerted by the independent variable on the dependent variable is 64.1% while the remaining 35.9% is influenced by other factors outside the model. Partially, work motivation is the dominant variable influencing employee performance.